Qualidade de cajus tratados com aminoetoxivinilglicina (AVG) e ácido geberélico (GA3) - Pontes Filho, Frederico Silva Thé (2014)
One of many problems that worry the cashew farmers is the very short post-harvest conservation of the peduncle, due to the fast firmness lost, negatively affecting the sales of this product. The use of growth regulators may be an alternative to improve the peduncle quality (keep flesh firmness), avoid waste (reduce the pre-harvest fall), increase the harvest time (reduce the seasonality), this way, dropping production costs in the cashew farming. The aim of this study was to evaluate the effect of AVG and GA3 spraying in pre-harvest, concerning the quality and production of pseudo fruits of dwarf cashew tree clones CCP 76 and 189, produced in the Northeast Brazilian Region. Thereunto, it was made five experiments, which the replications was the harvests times, for each treatment. The first was carried in randomized block, with two plants per unit and 10 fruits per plant, with following treatments (doses) for the CCP 76 clone: AVG 0 mg L-1 (water sprayed); AVG 40 mg L-1; AVG 80 mg L-1; AVG 120 mg L-1; GA3 40 mg L-1; GA3 80 mg L-1; and GA3 120 mg L-1. The studied characteristics was power of hydrogen (pH), soluble solids (SS), titratable acidity (AT), SS/AT relation, soluble sugar (AS), vitamin C (VC), total carotenoids (CT), total anthocyanins (ANT) and extractable polyphenols (PE). The second and the third experiments were carried in randomized blocks, with two plants per unit and 15 fruits per plant and two clones (CCP 76 and BRS 189). These experiments include the following treatments (doses): AVG and GA3 0 mg L-1 (water sprayed); 60 mg L-1, 120 mg L-1, 180 mg L-1 of AVG and 60 mg L-1, 120 mg.L-1, 180 mg.L-1 of GA3. For both clones the characteristics evaluated was break between spray and harvest, fruit fall before harvest, peduncle size, peduncle basal diameter, peduncle top diameter, cashew total mass, peduncle mass, nut mass and peduncle flesh firmness. The fourth and fifth experiments had same treatments and experimental set of the second and third. However the evaluated variables, for both clones, was: SS, AT, SS/AT relation, AS and VC. In the first experiment it was observed that the GA3 120 mg L-1 dose could be a alternative for the early dwarf cashew clone CCP 76, because it improved the commercial quality attributes of the peduncles. In the experiments two and three GA3 increased the break between the spraying and the harvest, the size and firmness of clones peduncles studied. In the two last experiments the GA3 increased the SS/AT relation of the peduncles of CCP 76 and BRS 189 early dwarf cashew clones. Therefore, besides it detain the maturation time, the growth regulators also improved some quality attributes of the peduncles, what is well wished due to the fact that the improvement of such attributes is predominantly made by genetic improvement, and this process, in the current conditions, takes a lot of time to be concluded.